Biaxial compressive behavior of embedded monolayer graphene inside flexible poly (methyl methacrylate) matrix. (May 2015) - Wang, Guorui; Liu, Luqi; Dai, Zhaohe; Liu, Qing; Miao, Hong; Zhang, Zhong
Abstract: We systematically investigated the in-plane biaxial compression behavior of the monolayer poly (methyl methacrylate) (PMMA)/graphene/PMMA system by in situ Raman spectroscopy. The shifts of Raman G-band peak position exhibited three-stage features with increasing compressive strain, including elastic deformation, local Euler-buckling and continuous compression. Our results demonstrated that the mechanical stability of graphene based flexible electrodes greatly depended on the deformation modes, applied strain level and interfacial adhesion. The embedded graphene sheets performed reversible compressibility at lower strain level over many cycles. With further increasing compressive strain, the strain distribution of the embedded graphene sheet turned non-uniform, and the interfacial debonding occurred. An analytical model based on the mechanical instability theory was proposed to depict the interfacial debonding behavior of individual graphene sheet, which agreed well with the experimental results.